Gel electrophoresis of proteins (Oxford University Press, 1998)
This text presents the best methods, hints and tips for core procedures such as one-dimensional polyacrylamide gel electrophoresis, isoelectric focusing, two-dimensional gel electrophoresis, preparative gel electrophoresis, and peptide mapping, with refinements and updates of the procedures.